Chalek Juice: An alternative diet therapy of diabetes mellitus - Yunianitamara, Vinna Maulidha; Widiastuti, Erma Nurjanah; Rahayu, Cucu; Sera, Agnescia Clarissa (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2022)
Not required.